Samorząd terytorialny w orzecznictwie Federalnego Trybunału Konstytucyjnego Republiki Federalnej Niemiec - Honka, Norbert (PRAWO i WIĘŹ, 2025)
The purpose of this paper is to highlight the role of the Federal Constitutional Court in defining the concept of local self-government in the Federal Republic of Germany. The reflection covers the process of the formation of the constitutional judiciary in Germany since the 19th century onwards, the role of the Federal Constitutional Court as guardia the constitutional order in Germany and the case law of the Federal Constitutional Court in defining local self-government.